The Shifting Role of Accountants in the Era of Digital Disruption - Mujiono, Mia Novinda (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
Pandemic and industrial revolution 4.0 made almost of all business activities and professional moved to digital way. People have to adapted to work with many innovations that emerged in the field of business which they work, including accountant. The era of digital disruption made the fundamental role of the accountant taken over by system or software. This phenomenon raises anxiety for a number of accountants, because their jobs are replaced by system, so companies can reduce the number of workers which classified as accountants. Whether the accountant will die along with the development of technological innovation? Certainly not. The purpose of this research is giving insight that accountants are required to be agile-learners who enrich skills with the aim of managing creativity and reasoning so that they are able to create infrastructure, platforms, and digital software that can control the automation in business. Using qualitative explanatory research method with literature review, observation, and interview, researcher found that the functional role of accountants is increasing, not only in financial reporting system proficiency, but especially in strategic business analysts with the help of business intelligence as the basis of decision making for business. Likewise technological innovation gave birth to another scientific field of business and accountant which enlarge job opportunities and threats as the results and implications. Keeping financial data and confidential information safe and secure should be the top priority for any business.